Usability Media Pembelajaran Geometri Berbasis GeoGebra untuk Meningkatkan Kemampuan Numerasi Mahasiswa - Junaidi, Junaidi; Pramestie Wulandari, Nourma (FKIP Universitas Mataram, 2024)
The problem in this study is how feasible the GeoGebra-based learning media developed to enhance students' numeracy ability . The objective of this research is to identify the aspects of GeoGebra-based geometry learning media that need improvement. The research employs a mixed-methods approach. The conclusion of this study is that the development of GeoGebra-based learning media should focus on improving accuracy and completeness of the material, alignment with the curriculum, relevance of examples and exercises, visual appearance, interaction, user-friendliness, and adequate technical support. There is a need for more precise, accurate, and comprehensive material presentation. Learning media should ensure that all topics are thoroughly covered according to the applicable curriculum. The content needs to be more aligned with current educational standards to ensure relevance and appropriateness. Examples of mathematics applications in daily life and interactive exercises can enhance students' understanding. The presentation structure should be more logical and organized to facilitate navigation and use by students. The use of interactive tools such as animations and quizzes can help users understand the material. Access time to the media should be accelerated, and visual appeal should be enhanced to attract students' interest in learning. Quick guides and brief tutorials should be available to assist new users.